Laparoscopic ureteral reimplantation in a renal transplant - Gregorio, Sergio Alonso y (Polish Urological Association, 2013)
We present what is to our knowledge, the first case of laparoscopic ureteral reimplantation reported in the renal transplant. The ureteral stenosis is one of the most difficult renal transplant complications to deal with. With the development of the endourological approach, this treatment has become the first treatment option for these patients. The patient is a 28-year-old female who received a renal allograft from a cadaver donor in 2008. Ureteral stenosis was diagnosed. The laparoscopic approach seems to be a good option over the open approach, with the benefits related with laparoscopic surgery.